The effect of instagram marketing and store image on purchase decision with gender as moderating variable - Mega Ningrum Suwarno Putri; Robiansyah Robiansyah; Heni Rahayu Rahmawati (Faculty of Economics and Business Mulawarman University, 2022)
This study aims to reveal the effect of instagram marketing and store image on purchase decision. In addition, this study also aims to find out how gender moderates the influence of instagram marketing and store image on purchase decision. This research was conducted in Samarinda, Indonesia with the respondents are smart phone buyers in Samarinda. The sampling method was purposive sampling technique with a total sample of 85 respondents. The hypothesis testing using Structural Equation Modeling with software of Smart-PLS (Partial Least Square). The results of this study indicate that instagram marketing and store image have positive and significant influence on purchase decision. However, this study shows that gender does not significantly moderate the relationship between internet marketing and store image on purchase decision of smart phone products.